ANALISIS PENGARUH KEPERCAYAAN DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE MELALUI FACEBOOK SEBAGAI MEDIA SOSIAL (Studi Kasus Pada Pondok Pesantren Luhur Wahid Hasyim Putri Semarang) - Aulia, Imam (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
The increasing public access to the Internet, especially on social media Facebook. Where in Facebook, provided space for sale and purchase transaction of a product. This means that there is a phenomenon concerning the purchase of products through the site online facebook developed in the community. Problem within this research are “What are the factors that can increase product purchasing decisions online through the social media facebook?”. This research especially investigate three variables were, trust and information quality. Aim of this research was to analyze influence of that two variables to both buying decision. By bibliography examination and hypothetic arrangement, data collected through questionnaire method to 100 people who never make purchases of products through the social media facebook by using nonprobability technique sampling. Then carried out analysis to the data obtained by using double regression analysis. This analysis including: both validity and reliability tests, classic assumption test, double regression analysis, hypothesis through t test and F test, and determination coefficient analysis (R2). From that analysis obtained regression equality: Y = 0,186 X1 + 0,626 X2 Whereas buying decision variable (Y), trust (X1) and information quality (X2). Hipotesis examination used t test showed that two independent variable researched significantly proved influence buying decision of dependent variable. Then through F test found that trust and information quality suitable to research dependent variable of buying decision. Adjusted R Square Number about 0,723 showed that 72,3 percent buying decision variable could described by second independent variables within regression equality. Whereas the remainder about 27,7 percent described by other variable out from third variable used within this research. Keywords : buying decision, trust, information quality